A new fossil mite from French Cretaceous amber (Acari: Heterostigmata: Nasutiacaroidea superfam. nov.), testing evolutionary concepts within the Eleutherengona (Acariformes). (2nd April 2016) - Sidorchuk, Ekaterina A.; Perrichot, Vincent; Lindquist, Evert E.
Abstract : We describe a fossil member of Heterostigmata of Late Cretaceous age that is the first to show an unexpected array of primitive and derived attributes, some of which are perplexing for a member of this specialized group of trombidiform mites. In contrast, previously published records of heterostigmatic mites of similar age have been of fossils readily classified within moderately derivative superfamilies of this clade. With remarkably preserved details visible, our fossil is a male, from amber of Early Santonian to Middle Cenomanian age ( c .85–97 Ma), from a deposit in the Department of Vendée in north-western France. A new genus and species, Nasutiacarus perplexus Sidorchuk & Lindquist, representing a new family and superfamily, are described. We discuss the most salient of the perplexing attributes, especially aspects of the gnathosoma, using them to emphasize the significance of parallel and convergent evolution amongst major groups of eleutherengone Trombidiformes. http://zoobank.org/urn:lsid:zoobank.org:pub:F6CF7838-126F-4196-BE38-77791299240E